Policy With an Asterisk: Understanding How Staff in Alternative School Settings Negotiate a Mandatory Attendance Policy to Meet the Needs of Their Students - Birioukov-Brant, Anton; Brant-Birioukov, Kiera (Frontiers in Education, 2019)
Compulsory school attendance is enacted legislation in every Canadian province. Provincial Ministry of Education attendance expectations trickle down to the school boards, which create mandatory attendance policies stipulating that students be present at school irrespective of their ability to attend. A body of literature has documented the numerous and often insurmountable obstacles many youths face with respect to consistently attending school. Issues that impede consistent attendance include abuse, poverty, violence, and mental health disorders. However, attendance policies do not pay credence to these issues. Rather, school educators are expected to follow the policies in their rigid conception. This creates tension for the educators, who are expected to uphold unilaterally imposed policies, and yet enact these policies in such a way that does not compromise their students' education. Educators working in alternative schools are often confronted with this moral dilemma because these schools serve high numbers of students often absent from school. As such, we sought to understand the professional and ethical tensions alternative high school staff experience when navigating the enforcement of mandatory attendance polices. This study was carried out in a large city in the Canadian province of Ontario, where the school board's attendance policy requires students over the age of 18 to be demitted from enrollment if they miss 12 consecutive days of school without a “legitimate” excuse. Semi-structured interviews with 16 staff members in four alternative high schools revealed the inherent difficulty of responding to the needs of students by allowing them to miss some school while also meeting the legal obligations of the mandatory attendance policy established by the school board. We argue that these alternative school educators are active policy makers in their own right, as they interpret, co-opt, appropriate, and negotiate the attendance policy with the realities of their students' lives.